Pokroky v lécbĕ karcinomu dĕlozního hrdla--3D plánování HDR brachyterapie pomocí CT/MR - Dolezel, M; Vanásek, J; Odrázka, K; Tichý, M (Ceska gynekologie, 2008)
Brachytherapy plays a major role in the therapeutic management of patiens with cervix cancer. The rapid dose fall-off provide a very high dose to the tumor, while relative sparing bladder, rektum, sigmoid and small bowel. The CT/MR-based planning provides better information on target and organ volumes and dose-volumes histograms in contrast to radiography-based planning, that provides doses only at selected points.
Keywords: magnetická rezonanční tomografie; Radiotherapy Dosage; brachyterapie; celková dávka radioterapie; Imaging, Three-Dimensional; Magnetic Resonance Imaging; Uterine Cervical Neoplasms; ženské pohlaví; Humans; počítačová rentgenová tomografie; nádory děložního čípku; Female; Radiotherapy Planning, Computer-Assisted; zobrazování trojrozměrné; Tomography, X-Ray Computed; lidé; Brachytherapy; plánování radioterapie pomocí počítače